Comparison of PCR assay with serum and whole blood samples of experimental trials for detection and differentiation of Brucella melitensis. - Takele, Belay Y.; Bejo, Siti Khairani; Bahaman, Abdul Rani; Omar, Abdul Rahman (Medwell Online, 2009)
Brucellosis poses a significant animal and public health problem in many developing countries and requires fast and accurate diagnosis. A PCR assay amplifying part of the Brucella melitensis specific IS711 gene was developed and applied to mice clinical samples on an experimental trial. Over an 8 week period of infection, whole blood and serum were examined from 78 experimental mice, with a total of 60 samples from B. melitensis infected mice and a group of 96 control samples from mice inoculated with Brucella abortus 544, Yersinia enterocolitica O:9 and Brucella broth. Regardless of date of infection, the sensitivity of whole blood and serum based PCR assay with samples from B. melitensis infected mice was found to be 100% (30/30) and 83.3% (25/30), respectively. Serum samples collected at 60 days post infection (p.i) of B. melitensis failed to show a positive result. An amplicon of 252 bp was obtained in all PCR positive samples. All samples obtained from the control groups tested negative, conferring an assay specificity of 100%. These results show that the use of serum-PCR may lead to assay simplification and shorten turnaround time, but the optimal clinical specimen for this test was not serum but whole blood, which leads to maximum assay sensitivity